How country names legitimize economic nationalism: a critical discourse analysis - Yongqi Wang; Yujie Xie (Discover Global Society)
Abstract This research presents a critical metaphor and metonymy analysis of how national names in economic reporting carry nationalist ideology and persuade public opinion. Adapting Charteris-Black’s Critical Metaphor Analysis (2004, 2018), this research analyzes the linguistic, conceptual and communicative level of the metaphoric and metonymic use of ‘China’ and ‘Australia’ in Australian media coverage of a high-profile transnational business deal. A consistent pattern of country for company metonymy and country is a person metaphor was identified to naturalize nationalist ideology in the business domain. The strategic use of these metonyms and metaphors can strengthen the argument by diverting attention from crucial facts, confusing business and political entities, and imposing national stereotypes. Contemporary economic nationalism reflects a globalization paradox where states maintain regulatory roles while facing constraints from global interdependencies, with discourse strategically blending market principles with national interests to maintain legitimacy. This study highlights how country names, as linguistic signifier of banal nationalism, provide the rhetorical foundation that underpins and legitimizes economic nationalist arguments and actions, particularly during trade disputes. Beyond the case study, our findings reveal the linguistic mechanisms through which seemingly neutral economic reporting legitimizes contemporary protectionist policies from Australia–China resource tensions to "America First" trade rhetoric in today's era of resurgent economic nationalism.